Spontaneous Pneumothorax Following Bronchopleural Fistula In Geriatric Patient: A Case Report And Emergency Management - Erwin, Ferdinand; Laksono, Gerardo AK; Sarvasti, Dyana; Tahalele, Paul L (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Introduction: Bronchopleural fistula (BPF) is a pathological connection between thebronchial tree and the pleural space. Clinical manifestation of BPF may be classified as acute,subacute, and delayed or chronic forms. Acute BPF can be a life-threatening condition due totension pneumothorax or asphyxiation from pulmonary flooding. Purpose: To report the patient survival from the upper lobe of the right lung bronchopleuralfistula wedge resection and to use staplers as upper lobe pulmonary wound closure. Case Report: 72-year-old male referred from pulmonologist with a chief complaint ofprogressive shortness of breath and nonproductive cough for four days. The patient had ahistory of tuberculosis and COPD and a heavy smoker for the last 50 years. Chestradiography showed a decreased opacity of the right hemithorax, with 40% collapsed of the lung parenchyma. Chest tube insertion performed on the right hemithorax, then the patient got immediate relief. On the seventh day, the patient complained of worsening dyspnea. Achest x-ray showed lung collapsed on the right hemithorax. Multislice CT-scan (MSCT) ofthe chest showed right-sided pneumothorax with bronchopleural fistula. Wedge resection forthe 3 cm in diameter fistula was performed. On the seventh day postoperative, the patient wasfully recovered then discharged from the hospital.Conclusion: Seven days postoperatively of wedge resection, the patient discharge from thehospital without any complication and stable hemodynamic. The patient went to theoutpatient department for follow up one week after.